Identification of a Large Family of Slam-Dependent Surface Lipoproteins in Gram-Negative Bacteria - Hooda, Yogesh; Lai, Christine C. L.; Moraes, Trevor F. (Frontiers in Cellular and Infection Microbiology, 2017)
The surfaces of many Gram-negative bacteria are decorated with soluble proteins anchored to the outer membrane via an acylated N-terminus; these proteins are referred to as surface lipoproteins or SLPs. In Neisseria meningitidis, SLPs such as transferrin-binding protein B (TbpB) and factor-H binding protein (fHbp) are essential for host colonization and infection because of their essential roles in iron acquisition and immune evasion, respectively. Recently, we identified a family of outer membrane proteins called Slam (Surface lipoprotein assembly modulator) that are essential for surface display of neisserial SLPs. In the present study, we performed a bioinformatics analysis to identify 832 Slam related sequences in 638 Gram-negative bacterial species. The list included several known human pathogens, many of which were not previously reported to possess SLPs. Hypothesizing that genes encoding SLP substrates of Slams may be present in the same gene cluster as the Slam genes, we manually curated neighboring genes for 353 putative Slam homologs. From our analysis, we found that 185 ( 52%) of the 353 putative Slam homologs are located adjacent to genes that encode a protein with an N-terminal lipobox motif. This list included genes encoding previously reported SLPs in Haemophilus influenzae and Moraxella catarrhalis, for which we were able to show that the neighboring Slams are necessary and sufficient to display these lipoproteins on the surface of Escherichia coli. To further verify the authenticity of the list of predicted SLPs, we tested the surface display of one such Slam-adjacent protein from Pasteurella multocida, a zoonotic pathogen. A robust Slam-dependent display of the P. multocida protein was observed in the E. coli translocation assay indicating that the protein is a Slam-dependent SLP. Based on multiple sequence alignments and domain annotations, we found that an eight-stranded beta-barrel domain is common to all the predicted Slam-dependent SLPs. These findings suggest that SLPs with a TbpB-like fold are found widely in Proteobacteria where they exist with their interaction partner Slam. In the future, SLPs found in pathogenic bacteria can be investigated for their role in virulence and may also serve as candidates for vaccine development.